In situ synthesis of Mo-doped carbon-coated NiCo2S4 nanosheet networks for supercapacitors - Wang, Kaiyu; Zhou, Fan; Chu, Jiangnan; Ouyang, Wenchong; Wang, Kun; Wu, Zhengwei (Electrochemistry communications, 2025)
•Double-layer carbon and NiCo2S4 form SC.•NiCo2S4 is in-situ grown on foam nickel for improved quality.•Effect of ion doping on NiCo2S4's electrochemical properties studied. Supercapacitors offer numerous advantages, including high power output, quick charging and discharging rates, and stable cycling performance. Nevertheless, their energy density and cycle life still fall short of current industry demands for energy storage. To address these challenges, this work fabricated nanostructured electrodes by synthesizing molybdenum-doped carbon-coated NiCo2S4 (C@NiCo2S4-Mo), using NiCo2S4 as the precursor. The doping of molybdenum, a transition metal with many oxidation states, significantly improved the electronic structure and stability of the electrode material. Additionally, incorporating a carbon-coated structure enhanced the material’s stability during cycling, extending its operational lifespan. The results demonstrated that C@NiCo2S4-Mo exhibited exceptional electrochemical properties, featuring a defined capacitance of 931.75 Farad/g under the current flux of 1 A/g. This high specific capacitance value, a vital factor regarding capacitor performance, directly influences the energy storage capacity of the device, indicating the high potential of the C@NiCo2S4-Mo material for supercapacitors. It was observed that the particular capacity retention was 76.6 % when the current density was increased by a factor of 10. The substance also showed favorable pseudocapacitive characteristics, retaining 87.7 % of its particular capacitance after prolonged cycling in cyclic voltammetry (CV) tests, highlighting its outstanding cyclic stability. Furthermore, supercapacitors constructed from C@NiCo2S4-Mo achieved an energy density of 14.5 Wh/kg at a power density of 700 kW/kg, making them promising candidates for energy storage applications.